EXSOLUTION OF MAGMATIC VOLATILE PHASES FROM CL-ENRICHED MINERALIZING GRANITIC MAGMAS AND IMPLICATIONS FOR ORE METAL TRANSPORT - Webster J.D. (My University, 1997)
To understand Cl dissolution in aluminosilicate liquids and the exsolution of Cl-rich magmatic volatile phases, experiments were conducted to determine the solubility of NaCl, KCl, and H2O in felsic liquids at 0.5 and 2 kbar. The Cl content of H2O-poor, NaCl-saturated, and KCl-saturated silicate liquids is low (i.e., =<1.3 wt%) to very low (i.e., ~0.2 wt%) and varies with changes in pressure and composition; the Cl concentration increases with the F concentration and the molar (Al + Na + Ca + Mg/Si) ratio of the liquid and decreases with increasing activity of H2O in the system.Exsolution of a volatile phase depends on the partial pressures of all dissolved volatiles, and low Cl solubilities in NaCl-saturated and KCl-saturated silicate liquids imply that exsolution of a Cl-bearing volatile phase will occur ''early'' in Cl-bearing granitic magmas, i.e., prior to extensive melt crystallization and/or at comparatively low water fugacities. The solubility behavior of H2O and Cl is very similar to that of CO2 and H2O in felsic liquids. Small quantities of CO2 are known to facilitate volatile phase exsolution (Holloway, 1976), and in a similar manner volatile phases may exsolve''early'' in Cl-enriched granite magmas. Whereas 5 to 6 wt% dissolved H2O is necessary for volatile phase exsolution from a CO2-free and Cl-free haplogranite liquid at 2 kbar and 800°C, a Cl-rich brine will exsolve if the liquid contains only 1 wt% H2O and 0.26 wt% Cl at the same conditions.These new solubility data are interpreted in light of H2O, F, and Cl concentrations in felsic liquids, determined from silicate melt inclusions, to constrain the exsolution of Cl-bearing, magmatic volatile phases from mineralizing granitic magmas. Felsic magmas genetically associated with Cu-porphyry and Mo-porphyry mineralization contain sufficient H2O and Cl to become saturated with respect to a hypersaline brine without strong pressure reduction, boiling of the volatile phase (i.e., exsolution of immiscible vapor and brine), or strong volatile enrichment resulting from extensive crystal fractionation.Experiments were also conducted to investigate the solubility of Mo in highly saline volatile phases coexisting with granitic liquids at 2 and 0.5 kbar. The apparent partition coefficient for Mo in the volatile phase(s) relative to silicate liquid, (D*Mo), is defined as [the computed concentration of Mo in a volatile phase or phases/the measured concentration of Mo in granite glass]. D*Mo ranges from 8 to 80 as the NaCl and KCl content of the volatile phase(s) increases from 15 to 90 wt%. Because Mo does not complex with Cl in aqueous fluids, it appears that Mo solubility may be a strong function of the activity of Na and K in alkali chloride-rich volatile phases.